Integrasi Vertikal Ke Belakang pada Peternakan Ayam Petelur: Analisis Kelayakan Investasi Rearing House di Senopati Farm - Indira Wafaa Nur; Ana Noveria (KOLONI, 2026)
This research aims to analyze the financial feasibility of a rearing house investment for layer chickens at Senopati Farm, a medium-scale poultry farm in South Lampung, and to identify the variable most sensitive to the investment's feasibility. The investment was undertaken in response to Senopati Farm's complete dependence on external suppliers for pullet chickens, which exposed the farm to price volatility, inconsistent biological quality, and supply uncertainty. This study applies a quantitative case study approach, using primary data from interviews with Senopati Farm's management and secondary data from the company's financial and operational records, government regulations, and Lohmann Brown management guidelines. Feasibility was assessed using four capital budgeting criteria, namely Net Present Value (NPV), Internal Rate of Return (IRR), Profitability Index (PI), and Payback Period (PP), discounted at a Weighted Average Cost of Capital (WACC) of 10.20%. Risk analysis was conducted using sensitivity analysis with a tornado diagram and a Monte Carlo simulation of 1,000 iterations to evaluate the impact of uncertainty on investment feasibility. The results show that the rearing house investment is financially feasible, generating an NPV of Rp2,196,969,499, an IRR of 35.18%, a PI of 3.19, and a payback period of 2 years and 22 days, all within the ten-year project lifetime. Grower feed price was identified as the most sensitive variable, capable of turning the project's NPV negative with a 20% price increase. The study concludes that Senopati Farm's backward vertical integration decision creates financial value, though its sustained performance depends on management's ability to control feed price risk exposure.